What's happening to our universities?. (2nd January 2016) - Martin, Ben R.
Abstract: In recent decades, many universities have been moving in the direction of a more hierarchical and centralised structure, with top-down planning and reduced local autonomy for departments. Yet, the management literature over this period has stressed the numerous benefits of flatter organisational structures, decentralisation and local autonomy for sections or departments. What might explain this paradox? And why have academics remained strangely quiet about this, meekly accepting their fate? This proposition paper critically examines the dangers of centralised top-down management, increasingly bureaucratic procedures, teaching to a prescribed formula, and research driven by assessment and performance targets, illustrating these with a number of specific examples. It discusses a number of possible forces driving these worrying developments, and concludes by asking whether academics may be in danger of suffering the fate of the boiled frog.